2009
DOI: 10.1093/rpd/ncp245
|View full text |Cite
|
Sign up to set email alerts
|

Photon doses at the entrance of 60Co and low-energy medical accelerator rooms under unusual irradiation conditions

Abstract: In this paper, the general-purpose Monte Carlo code MCNP5 was used to study the dose variance due to the position of medical linear accelerators, under unusual conditions, for shielding design of radiotherapy facilities. It was found that the computational methods generally used to estimate the scattered photon doses at the entrance of radiotherapy unit vaults provide conservative results when compared with the MCNP results, considering the standard condition. On the other hand, for the situations where the ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In many cases the facilities were subjected to nonauthorized project changes, or the person responsible for the facility decided to utilize a higher activity 60Co source not appropriate to the existing approved irradiator bunker shielding . ( 21 ) Another possible reason is a 60Co unit was positioned at an unusual configuration (for instance, forming angles about 45° with the bunker walls), a situation that can generate higher dose rates in the neighborhood of the treatment room (22) …”
Section: Resultsmentioning
confidence: 99%
“…In many cases the facilities were subjected to nonauthorized project changes, or the person responsible for the facility decided to utilize a higher activity 60Co source not appropriate to the existing approved irradiator bunker shielding . ( 21 ) Another possible reason is a 60Co unit was positioned at an unusual configuration (for instance, forming angles about 45° with the bunker walls), a situation that can generate higher dose rates in the neighborhood of the treatment room (22) …”
Section: Resultsmentioning
confidence: 99%
“…A variant of this problem was previously investigated by Facure et al where they studied the effects of photon dose-equivalent at the vault door from "unusual" gantry orientations [2]. They found that an increase by up to a factor of 7 for photon dose-equivalent could be achieved by orienting the gantry at 45˚ to the maze normal, but that photon dose-equivalent was reduced by approximately a factor of 2 by pointing the gantry directly towards the maze.…”
Section: Introductionmentioning
confidence: 99%
“…Desde o advento da teleterapia, tanto as técnicas de tratamento quanto de equipamentos melhoram significativamente e protocolos foram estabelecidos tanto para os operadores, quanto para o público alvo devido à exposição à radiação. Muitas publicações têm sido avaliadas ao longo dos anos para elucidar os efeitos destas mudanças nas técnicas protetoras (FACURE et al, 2010).…”
Section: 2-terapia Multimodal Para O Tratamento De Câncer Esofágicounclassified
“…Exercício de resistência associado à lesão muscular induz a resposta inflamatórias maior (NIEMAN, 2000). A utilização dos métodos de imunohistoquímica e bioquímica para a avaliação das citocinas pró-inflamatórias pulmonares tem sido usada há muito com sucesso (ESCOTTE et al, 2003;RABBANI et al, 2005;LEE et al, 2006b;FENG et al, 2008;KIM et al, 2008;ZHAO et al, 2008;CHEN et al, 2009;KIM et al, 2009;CHEN et al, 2010;MOON et al, 2010). Em alguns outros estudos, a utilização do sangue periférico para a avaliação da expressão de tais citocinas não se mostrou eficaz, como, por exemplo, o estudo realizado por MORITA et al…”
Section: Extração De Tecido E Análise Protéica Por Immunoblottingunclassified